1969
DOI: 10.1007/bf00386459
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ammonium on nitrate reduction in wheat seedlings

Abstract: Ammonium markedly inhibited nitrate absorption by nitrogenstarved wheat seedlings but did not decrease the proportion of absorbed nitrate that was reduced. Seedlings high in nitrate (absorbed prior to the experimental periods) reduced similar amounts of this nitrate regardless of whether or not ammonium was present and being absorbed during the period of measurement. Ammonium or products of ammonium assimilation did not interfere with the induction, stability, or activity of nitrate reductase. Consequently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…The light intensity was 194 hectolux at plant height, and temperature was 24 +2 C and 17 + 2 C during the light and dark periods, respectively. These growth conditions produced seedlings low in nitrogen and high in carbohydrate content (16). Thus the seedlings would be expected to absorb and assimilate nitrate nitrogen at a rapid rate, provided the required transport, reduction, and assimilatory systems were present.…”
Section: Methodsmentioning
confidence: 99%
“…The light intensity was 194 hectolux at plant height, and temperature was 24 +2 C and 17 + 2 C during the light and dark periods, respectively. These growth conditions produced seedlings low in nitrogen and high in carbohydrate content (16). Thus the seedlings would be expected to absorb and assimilate nitrate nitrogen at a rapid rate, provided the required transport, reduction, and assimilatory systems were present.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the work of MINOTTI et a/. (8) suggested that NH, + can influence the N0 3 -uptake process directly rather than indirectly via its effect on N0 3 -reductive activity.…”
mentioning
confidence: 91%
“…When present in the external medium, NH4' is a potent inhibitor of NO3-uptake by barley plants (15, 25), and of N03 accumulation in several other species, including wheat (19,20) ryegrass (2, 16), apple (10), and corn (23). It should be stressed, however, that a reduction of NO3-accumulation by NH4' might be caused by effects upon NO3-translocation or reduction rather than via direct effects on NO3-uptake per se.…”
Section: Introductionmentioning
confidence: 99%
“…Both short term (direct) effects of NH4' on the activities of the nitrate transporter, as well as long term (indirect) effects, possibly via transcription-dependent events, might be envisioned. In addition, exposure oftissues to products of NO3-assimilation, the amino acids, would be anticipated to influence rates of NO3-uptake.When present in the external medium, NH4' is a potent inhibitor of NO3-uptake by barley plants (15, 25), and of N03 accumulation in several other species, including wheat (19,20) ryegrass (2, 16), apple (10), and corn (23). It should be stressed, however, that a reduction of NO3-accumulation by NH4' might be caused by effects upon NO3-translocation or reduction rather than via direct effects on NO3-uptake per se.…”
mentioning
confidence: 99%